Validitas Beton Mutu Tinggi Menggunakan Komparasi Campuran Bahan Feldspar terhadap Kuat Lentur - Rio Rahma Dhana; Dwi Kartikasari; Wulandari Wulandari (Pusat riset dan Inovasi Nasional, 2026)
The development of science and technology generally brings positive impacts in terms of convenience in various human activities, but on the other hand, it also leads to negative consequences such as an increase in waste. One of the significant wastes produced from construction activities, including building and house construction, is feldspar, which typically comes from leftover ceramic materials. Feldspar is a type of waste that is difficult to decompose naturally and has no economic value, often accumulating and polluting the environment. Therefore, innovation is needed to utilize this waste to create value. This study aims to use feldspar powder as a replacement for fine aggregates in K-200 grade concrete mixtures. The research method involved mixing feldspar powder in specific proportions as a substitute for sand, followed by a series of tests, including compressive strength and flexural tests, to determine the feasibility and performance of the resulting concrete. The results indicate that the use of feldspar powder as a fine aggregate produces a concrete mixture with satisfactory mechanical characteristics, meeting the K-200 concrete standards. These findings not only provide an alternative environmentally friendly material but also offer a solution to reduce ceramic waste, contributing positively to sustainable construction.